Association between Anatomic Configuration of Thrombosis with Clinical Symptoms and Risk factors in Admitted Patients with Deep Vein Thrombosis - Bozorgmehr, Rama; Karimi Toudeshki, Kimia; Saadati, Nasrin; Ehsanfar, Nasrin; Pishgahi, Mehdi (Archives of Men's Health, 2021)
Introduction: Deep vein thrombosis (DVT) is prevalent and challenging for physicians. Previously, the clinical symptoms of DVT are different based on the location of the thrombosis. In this study, the anatomic location of thrombosis and its relation with clinical symptoms and DVT risk factors were investigated. Methods: In this retrospective study, the hospital documents of 204 patients with acute lower extremity DVTs in Shohada-e-Tajrish hospital were reviewed from April 2020 to February 2021. The diagnosis was confirmed using Doppler ultrasound. Based on the location of the thrombosis, the patients were divided into four groups: unilateral proximal group (UPG), bilateral proximal group (BPG), unilateral distal group (UDG), and ipsilateral proximal and distal group (IPDG). Finally, the frequency of risk factors and symptoms were compared between the groups. Results: In this retrospective study, 204 patients with the diagnosis of acute lower extremity DVTs at the time of hospitalization or during hospitalization were studied. The mean±SD age of the patients was 57.1±19.2 years (range: 12-98 years). Of these, 114 (55.9%) were men and 90 (44.1%) were women. There were 174 patients in UPG, 16 in BPG, 5 in UDG and 9 in IPDG. In total, 97.5% of the patients had proximal thrombosis while only 6.9% of them had distal thrombosis. The incidence of different limb circumferences was significantly higher in UPG and IPDG compared to BPG and UDG (P<0.05). There was no statistically significant difference between groups in terms of other symptoms and risk factors. Conclusion: Most of the DVTs were found in the proximal veins of the lower extremities. It seems that these DVTs are more likely to create edema compared to others and in unilateral cases may result in different circumferences of the lower limbs. But there was no significant association between other clinical signs of DVT including limb pain, edema, erythema, palpitations, and shortness of breath with thrombosis location. Also not significant association between DVT risk factors and the location of thrombosis were found.